Staying strong: Exploring experiences of managing emotional distress for African Caribbean women living in the UK. (February 2021) - Graham, Rachel; Clarke, Victoria
The "strong Black woman" (SBW) is a Western cultural stereotype that depicts African-heritage women as strong, self-reliant, independent, yet nurturing and self-sacrificing. US research indicates that this stereotype negatively impacts the emotional wellbeing of African-heritage women, while also allowing them to survive in a racist society. UK research has documented the significance of this stereotype in relation to African Caribbean women's experience of depression around the time of childbirth and "attachment separation and loss". However, research is yet to explore how UK African Caribbean women make sense of and negotiate the SBW stereotype in relation to their emotional wellbeing more broadly. Using five focus groups, with a total of 18 women, this research explored how these women experienced and managed emotional distress in relation to the SBW stereotype. The importance of "being strong" consistently underpinned the participants' narratives. However, this requirement for strength often negatively impacted their ability to cope effectively with their distress, leading them to manage it in ways that did little to alleviate it and sometimes increased it. This study offers important implications for understanding the experiences of emotional distress for UK African Caribbean women.